PERAN BELAJAR BERDASAR REGULASI DIRI DAN PENYESUAIAN DIRI TERHADAP PRESTASI BELAJAR SISWI MADRASAH TSANAWIYAH MUALLIMAT YOGYAKARTA - Damayanti, Eka (Jurnal Biotek, 2015)
The purpose of this study is to determine the role of self-regulated learning and self-adjustment in learning achievement. The research subjects are consisted of 121 first grade students (ages 12-14 years) at one junior secondary schooling Yogyakarta. The research measurement scales are consisted of self-regulated learning and self-adjustment. The learning aachievement data are collected from the student card report.  Data analysis was done by using multiple regression analysis with the help of SPSS computer program. The analysis result shows that self regulated learning and self adjustment jointly have a significant role on student achievement (F-value of 3.089 significance probability value of 0.049,p < 0.05) Based on the partial test, it can be seen that the self regulated learning variables and self-adjustment variables separately had no significant role of student achievement. It can be seen from the probability values of significance respectively of 0.496 (p > 0.05) and 0.072 (p > 0.05).